Tensile properties, micro hardness and rupture surface images of aluminium 2024 wire Directed Energy Deposited material - Eimer, Eloise (Cranfield University, 2023)
This file provide the results of mechanical testing of the 2024 alloy deposited using the wire Directed Energy Deposition process.The scanning electron microscope images of representative rupture surface of each conditions tested are also provided.